Effects of maceration length after prefermentative cold soak: Detailed chromatic, phenolic and sensory composition of cabernet sauvignon, malbec and merlot wines - Casassa, Luis Federico (2021)
Cabernet Sauvignon, Malbec and Merlot grapes were processed with prefermentative cold soak (CS) for 5 days followed by a short maceration time of 5 days (CS + 5d), or a long maceration time of 10 days (CS + 10d). CS did not affect the basic chemistry of the wines, nor improved anthocyanins, polymeric pigments and total phenolics relative to Control wines (10 days maceration). Wine tannins were lowered in CS + 5d wines by 71 % (Cabernet Sauvignon) and by 29 % (Merlot). CIELab coordinates showed a negative impact on L*, C*, and copigmentation in CS wines indicating that these wines were lighter in color than their Control counterparts and these differences could be distinguished by the human eye. Astringency and bitterness were lower in CS + 5d wines, whereas CS + 10d wines showed enhanced fresh fruit aroma, body, bitterness, and astringency.